Pendampingan Pengolahan Nuget Ikan Udang Pada Kelompok Sasaran Stunting Diwilayah Desa Tedunan - Cahyanti, Luluk; Alvi Ratna Yuliana; Vera Fitriana; Devi Setya Putri (JEUMPA: Jurnal Pengabdian Kepada Masyarakat, 2024)
ABSTRACT The characteristics of the participants in this community service activity are dominated by female participants. Based on the characteristics of the role, most of the participants who took part in counseling were pregnant women, toddlers, school-age children, adolescents, women of childbearing age (catin). From the results of the counseling evaluation, counseling regarding stunting counseling and balanced nutrition with the processing of shrimp fish nuggets in the Tedunan village received a very good response, marked by the enthusiasm of the participants through questions related to stunting. Regarding the fulfillment of balanced nutrition with the development of local food products, the processing of fish nuggets also received a fairly good response. Keywords: Stunting, Nuget processing assistence